2023
DOI: 10.1002/app.53650
|View full text |Cite
|
Sign up to set email alerts
|

Regulation binary electromagnetic filler networks in segregated poly(vinylidenefluoride) composite for absorption‐dominated electromagnetic interference shielding

Abstract: Excellent conductivity and optimized impedance matching are vital for superior absorption-dominated electromagnetic interference (EMI) shielding. An efficient binary electromagnetic filler network regulation method has been proposed. Poly-(vinylidenefluoride)-ferroferric oxide-reduced graphene oxide/ single-wall carbon nanotube (PVDF-Fe 3 O 4 -RGC) composite has been synthesized as a layered segregated polymer composite structure by using an electrostatic assembly and hot compression strategy. Binary electroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…In addition, this study is aimed to construct absorption-dominated EMI shielding materials by in situ growth of Fe 3 O 4 in a porous conductive network structure, and to better explore the effectiveness of this scheme, the comparison of EMI SE and Ar of the GCF composite foams with other reported materials is investigated in a microwave frequency range of 8.2–12.4 GHz (shown in Figure ). The materials involved in the comparison contained all conductive fillers and Fe 3 O 4 particles and were all introduced into Fe 3 O 4 particles by other methods, such as co-blending. , It can be found that the EMI SE and Ar of GCF4 are significantly higher than those of some reported materials. Although the EMI SE of some materials is higher than that of GCF4, their Ar needs further improvement.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this study is aimed to construct absorption-dominated EMI shielding materials by in situ growth of Fe 3 O 4 in a porous conductive network structure, and to better explore the effectiveness of this scheme, the comparison of EMI SE and Ar of the GCF composite foams with other reported materials is investigated in a microwave frequency range of 8.2–12.4 GHz (shown in Figure ). The materials involved in the comparison contained all conductive fillers and Fe 3 O 4 particles and were all introduced into Fe 3 O 4 particles by other methods, such as co-blending. , It can be found that the EMI SE and Ar of GCF4 are significantly higher than those of some reported materials. Although the EMI SE of some materials is higher than that of GCF4, their Ar needs further improvement.…”
Section: Resultsmentioning
confidence: 99%
“…The coaxial transmission line method has emerged as the most widely adopted approach for measuring EMI SE, owing to its broad frequency measurement range, superior test repeatability, and comparability of results across different equipment 53 . The major advantage of this method lied in its capability to measure the EMI shielding performance of a given sample across a wide frequency range from 2 to 18 GHz.…”
Section: Emi Shielding Mechanisms and Its Measurement Techniquesmentioning
confidence: 99%
“…The recent studies of segregated-structured electromagnetic shielding materials are summarized in Table 3. Zhang et al [150] prepared PVDF/Fe 3 O 4 -RGC composite using layered electrostatic assembly and hot pressing. Wu et al [151] obtained Fe 3 O 4 @PA6/MWCNT composite with layer-adding manufacturing and molding.…”
Section: Segregated Structurementioning
confidence: 99%